Study of the effect of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)- 4H-1,2,4-triazole-3-yl)thio)acetate toxic doses on rats heart tissue - A. A. Safonov; O. I. Panasenko; N. A. Al Khalaf (Zaporozhye State Medical University, 2024)
Analysis of medicinal product safety is an important stage on the way to the entry of a synthetic compound into the pharmaceutical market. Along with the study of blood composition, scientists are actively analyzing the effect of toxic doses on the tissues of internal organs. Analyzing the toxic effect of compounds on heart tissue allows us to find out what damage substances can cause, which can have a direct impact on human health. Today, 1,2,4-triazole derivatives are very relevant and a huge number of publications is a confirmation of this. The aim of the work was to analyze the effect of toxic doses of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate on rats heart tissue. Materials and methods. Sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)acetate (ASP) was selected as the subject of investigation and administered intragastrically in the form of a suspension with purified water using a specialized metal probe. The toxic effect on tissues was analyzed using doses of 1000 mg/kg, which is 10 times higher than a single dose typically used in pharmacological activity studies, and 5000 mg/kg, which represents the limit for determining acute toxicity and the maximum dose within the fourth class of toxicity, considering the route of administration, provided that this dose does not result in the death of the animal. Analysis of the effect of toxic doses of ASP was performed on 12-month-old purebred male rats kept under standard conditions. Rat heart tissues were fixed for further histological examination in a 10 % formaldehyde solution, dehydrated in alcohols of increasing strength, and embedded in paraffin. Results. Macroscopic and microscopic analysis of rat heart tissue was carried out. The research shows the histological results of deviations from the norm for a group of rats that were injected with substances in the studied doses. Conclusions. The effect of toxic doses of ASP on rat heart tissue was analyzed. For a dose of 1000 mg/kg, local signs of protein dystrophy of cardiomyocytes and single loci of hemorrhages are observed. As for the dose of 5000 mg/kg, the effect of the substance on the heart tissue is more profound and is determined by the selective damage of cardiomyocytes with the loss of lumbar striation and the acquisition of a wave-like shape, full blood is observed in the ectasized capillaries.